Diseño de un plan estratégico para las PYMES del sector de bares y expendio de bebidas alcohólicas de la localidad de chapinero, Bogotá, para incrementar su competitividad y perdurabilidad (2015)
The project presents a description of the processes of implementation of a strategic plan for the economic sector of bars, taking into account findings in the field and highlighting the best strategies of some establishments Also, some issues within the bars, in order to find the main sources of risk that may affect them in the search for sustainability and competitiveness, were analyzed.